Simultaneous nitrate and phosphate removal from wastewater lacking organic matter through microbial oxidation of pyrrhotite coupled to nitrate reduction. (1st June 2016) - Li, Ruihua; Morrison, Liam; Collins, Gavin; Li, Aimin; Zhan, Xinmin
Abstract: This study investigated the efficiency of a pyrrhotite autotrophic denitrification biofilter (PADB) technology for simultaneous N and P removal from wastewater lacking organic matter. A PADB was constructed with natural pyrrhotite as the biofilter medium and inoculated with autotrophic denitrifies enriched from anaerobic sludge. Over an operating period of 247 days, PADB efficiently removed NO3 − and PO4 3− simultaneously from wastewater that lacked organic matter. The hydraulic retention time (HRT), and influent NO3 − and PO4 3− concentrations affected the removal of NO3 − and PO4 3− . A longer HRT led to lower concentrations of NO3 − and PO4 3− in the effluent. The PO4 3− removal was influenced by NO3 − removed; the more NO3 − removed, the more PO4 3− removed. As the synthetic wastewater containing NO3 − –N of 28 mg L −1 and PO4 3− –P of 6 mg L −1 in the absence of organic matter was treated by PADB at HRT of 24 h, total oxidized nitrogen (TON; NO2 − –N + NO3 − –N) and PO4 3− –P concentrations of effluent were as low as 1.13 and 0.28 mg L −1, respectively. When treatment of municipal wastewater treatment plant (WWTP) secondary effluent with TON of 21.11 mg L −1 and PO4 3− –P of 2.62 mg L −1 at HRT of 24 h, the effluent TON was 1.89 mg L −1 and PO4 3− –P was 0.34 mg L −1 . PO4 3− was removed through the formation of secondary minerals with Fe and Ca. These secondary minerals contained elevated phosphorus, which presents a potential for P recovery from wastewater. Graphical abstract: Highlights: N and P were simultaneously removed from wastewater lacking organic matter. NO3 was reduced by autotrophic denitrification with pyrrhotite as the electron donor. Phosphate was mainly removed through formation of secondary minerals with Fe 3+ . N and P levels in wastewater can be reduced to 1.13 and 0.3 mg L −1, respectively.